IMPLEMENTASI MANAJEMEN PENDIDIKAN BERBASIS SEKOLAH DI PERGURUAN TINGGI - A.Y. Soegeng Ysh. Fakultas Ilmu Pendidikan IKIP PGRI Semarang (Magister Manajemen Pendidikan, Universitas PGRI Semarang, 2012)
Abstract. School-Based Management on Education or usually call as School-Based Management only part of new paradigm on education as antitesis of the previous paradigm, also as review of negative trends on global era. SBM as form of school autonomy, as matifestation of education autonomy, as a part of implementation of district autonomy. SBM use to empower school by working togather among parents, society, and government to improve quality of education. The implementation on higher education are on academic quality assurance as a function of SBM. It is recomended that SBM included on teacher training college curriculum. Abstrak. Manajemen Pendidikan Berbasis Sekolah yang disingkat menjadi Manajemen Berbasis Sekolah (MBS) merupakan sebagian dari paradigma baru manajemen pendidikan sebagai antitesis paradigma lama tetapi sekaligus bertugas mewaspadai kecenderungan-kecenderungan era global yang negatif. MBS sebagai bentuk otonomi sekolah, manifestasi dari otonomi pendidikan, sebagai bagian dari pelaksanaan otonomi daerah. MBS berfungsi memberdayakan sekolah melalui kerjasama dengan orangtua, masyarakat, dan pemerintah untuk meningkatkan mutu pendidikan. Implementasinya dalam tingkat perguruan tinggi berupa penjaminan mutu akademik sebagai fungsi MBS. Disarankan MBS masuk dalam kurikulum LPTK. Keywords: School-Based Management-SBM, new paradigm or education, autonomy, qualitu assurance.